2014
DOI: 10.1007/s11483-014-9382-z
|View full text |Cite
|
Sign up to set email alerts
|

Cold Plasma: A novel Non-Thermal Technology for Food Processing

Abstract: In the past cold plasma is used for sterilization of sensitive materials and now it is extended to food industries as a novel technology. For years cold plasma processing has been viewed as useful for microbial inactivation while maintaining quality of fresh produce. However, this process is not effective for in vitro model food systems for inactivation of microbes or enzymes which are present in intact tissues, as it is a surface phenomenon. Cold plasma technology is also used to inactivate endogenous enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
249
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 452 publications
(261 citation statements)
references
References 107 publications
5
249
0
7
Order By: Relevance
“…showed that the cold plasma affected the hardness of parboiled rice and decreased according to plasma power and time of treatment. Thirumdas, Sarangapani, et al (2015) also reported a similar decrease in hardness. Plasma treatments can be used effectively to reduce the cooking time required for BR (Chen, 2014).…”
Section: Hardnessmentioning
confidence: 60%
See 1 more Smart Citation
“…showed that the cold plasma affected the hardness of parboiled rice and decreased according to plasma power and time of treatment. Thirumdas, Sarangapani, et al (2015) also reported a similar decrease in hardness. Plasma treatments can be used effectively to reduce the cooking time required for BR (Chen, 2014).…”
Section: Hardnessmentioning
confidence: 60%
“…However, the plasma treatment may also result in changes in sensory property of food products which should be overcome Yong et al, 2015). Thirumdas, Sarangapani, and Annapure (2015) showed that there are several fields in the food-processing sector where cold plasma can be successfully applied to food products.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has demonstrated significant antimicrobial effects for biological applications [24][25][26]. Process efficacy of cold plasma for microbial inactivation, packaging modification, pesticide dissipation and wastewater treatment has been recently reviewed [19,[27][28][29][30]. As a novel treatment technology, plasma oxidation offers several advantages in the production of oxidising species such as radicals (e.g., H, O, OH • , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the full potential of non‐thermal atmospheric plasma remains untapped with numerous possible food applications. Non‐thermal atmospheric plasma has been used on several fresh fruit and vegetable produce, packaging materials and edible films with encouraging findings (Misra, Keener, Bourke, Mosnier, & Cullen, ; Pankaj et al, ; Pankaj, Bueno‐Ferrer, et al, ; Thirumdas, Sarangapani, & Annapure, ). Non‐thermal atmospheric plasma effect on orange (Almeida et al, ; Shi et al, ), pomegranate (Herceg et al, ; Kovačević, Kljusurić, et al, ; Kovačević, Putnik, et al, ), chokeberry (Kovačević, Kljusurić, et al, ; Kovačević, Putnik, et al, ) apple (Surowsky, Fröhling, Gottschalk, Schlüter, & Knorr, ) and white grape (Pankaj, Wan, Colonna, & Keener, ) juices have been studied previously.…”
Section: Introductionmentioning
confidence: 99%